Production and Characterization of Biodiesel from Malapari Seed Oil (Pongamia pinnata L.): Evaluation of Quality Parameters Based on the Indonesian National Standard (SNI) 04-7182-2015 - Taebenu, Desi Adriyanti Nina; Arpiwi, Ni Luh; Astarini, Ida Ayu (UI Scholars Hub, 2025)
This study produced biodiesel from Malapari seed oil (Pongamia pinnata L.) by optimizing the esterification and transesterification processes. The objectives of this study were to determine the sulfuric acid (H2SO4) catalyst concentration in the esterification reaction that can reduc the free fatty acid (FFA) content of the seed oil to ≤2%, analyze the oil to methanol molar ratio (i.e.,1:6, 1:9, and 1:12) and KOH concentration (i.e.,2%, 4%, and 6%) that will produce the highest biodiesel yield, and evaluate the quality of the produced biodiesel according to the Indonesian National Standar (SNI) 04-7182-2015. The research was conducted from October to December 2023 at the Plant Physiology Laboratory and the Physical Chemistry Laboratory, FMIPA, UNUD. The research applied Completely randomized design. Quantitative biodiesel data were analyzed using Analysis of Variance. If significant differences (α < 0.05) were detected, then the quantitative biodiesel data were further analyzed using Duncan's Post Hoc Test. Results showed that an H2SO4 concentration of 7% reduced the FFA content to 1.915%. A molar ratio of 1:12 with a 2% KOH catalyst produced the highest biodiesel yield of 65.35%. The produced met the SNI for the saponification number (i.e., 52.82–133.69 mg-KOH/g), iodine number (i.e.,7.19–22.42 g_I2/100_g), and cetane number (i.e., 86.48–132.68). However, the water content (i.e., 0.721%–2.407%), viscosity (i.e., 1.73–6.18 mm²/s), acid number (i.e., 0.224–4.685 mg_KOH/g), density (i.e., 874–917 kg/m³), FFA content (i.e., 0.116 -% to 2.229%), and methyl ester content (48,13% to–132.12%_mass) partially did not meet the standards. This study highlights the potential of Malapari seed oil as a biodiesel feedstock, with further required needed to meet all quality standards.